Carrier status for the common R501X and 2282del4 filaggrin mutations is not associated with hearing phenotypes in 5,377 children from the ALSPAC cohort. - Santiago Rodriguez; Amanda J Hall; Raquel Granell; W H Irwin McLean; Alan D Irvine; Colin N A Palmer; George Davey Smith; John Henderson; Ian N M Day (PLoS ONE)
Background Filaggrin is a major protein in the epidermis. Several mutations in the filaggrin gene (FLG) have been associated with a number of conditions. Filaggrin is expressed in the tympanic membrane and could alter its mechanical properties, but the relationship between genetic variation in FLG and hearing has not yet been tested. Methodology/principal findings We examined whether loss-of function mutations R501X and 2282del4 in the FLG gene affected hearing in children. Twenty eight hearing variables representing five different aspects of hearing at age nine years in 5,377 children from the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort were tested for association with these mutations. No evidence of association was found between R501X or 2282del4 (or overall FLG mutation carrier status) and any of the hearing phenotypes analysed. Conclusions/significance In conclusion, carrier status for common filaggrin mutations does not affect hearing in children.